2017
DOI: 10.18632/oncotarget.16096
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of multiple lung cancers: Discrimination between primary and metastatic lung cancers by genomic profile

Abstract: In cases of multiple lung cancers, individual tumors may represent either a primary lung cancer or both primary and metastatic lung cancers. Treatment selection varies depending on such features, and this discrimination is critically important in predicting prognosis. The present study was undertaken to determine the efficacy and validity of mutation analysis as a means of determining whether multiple lung cancers are primary or metastatic in nature. The study involved 12 patients who underwent surgery in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 30 publications
1
54
1
Order By: Relevance
“…Finally, the number of targeted genes in our NGS panel may be relatively small. Recent studies on mutational analysis using NGS have included a larger number of targeted genes than we did . Begg et al indicated that at least 20 markers are required from a statistical perspective to distinguish between clonal and independent tumors with high accuracy .…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Finally, the number of targeted genes in our NGS panel may be relatively small. Recent studies on mutational analysis using NGS have included a larger number of targeted genes than we did . Begg et al indicated that at least 20 markers are required from a statistical perspective to distinguish between clonal and independent tumors with high accuracy .…”
Section: Discussionmentioning
confidence: 93%
“…With the advances in high‐throughput sequencing technologies, mutational analysis for specific driver and suppressor genes has been shown to be useful for distinguishing between multiple primary tumors and pulmonary metastases . In recent years, in patients with MLC, several reports have been published of mutational analyses by NGS, which allows analysis for multiple gene mutations at once . In this study, we investigated the mutational profiles by NGS of 20 lung cancer‐related genes in surgically resected paired tumors obtained from the same patients and compared the clinicopathological diagnoses with the diagnoses based on mutational evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The total amount of DNA used for next-generation sequencing analysis was 1.62 ng of the biopsy specimens and 3.76 ng of the surgical specimens (Table S1). An assay system that could analyze the entire exon region of the 53 lung cancerrelated genes (68,046 amino acids) was developed in house, and the samples were subjected to next-generation sequencing (5)(6)(7). This assay system was used to identify mutations in the 53 significantly mutated genes, which were identified from 408 patients with lung cancer by total exon analysis (8,9).…”
Section: Case Presentationmentioning
confidence: 99%